Liquid coating as well as preparation method and application thereof

By using optimized liquid coatings, combined with hydroxyl ultra-weathering polyester resin and modified weathering polyester resin, the problem of high weight and high cost of photovoltaic module packaging materials is solved, and the flexibility, lightweight, low cost and improved performance of photovoltaic modules is achieved.

CN119505654APending Publication Date: 2025-02-25ZHONGHAN NEW MATERIAL TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202311037255.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing photovoltaic module packaging materials have problems such as large weight, high cost, insufficient performance and single appearance, which are difficult to meet the requirements of architectural aesthetics and technical standards.

Method used

A liquid coating is used, and the composition includes hydroxyl ultra-weathering polyester resin, modified weathering polyester resin and curing agent. By optimizing the coating components and process conditions, the flexibility, light transmittance and adhesion of the coating are improved.

Benefits of technology

It realizes the flexibility and lightweight of photovoltaic modules, meets technical standards such as ultraviolet resistance, anti-aging, impact resistance, and fire resistance, and improves production efficiency and product aesthetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a liquid coating, raw materials for preparing the liquid coating comprise thermosetting resin A, thermosetting resin B and a curing agent, the thermosetting resin A is hydroxyl super-weather-resistant polyester resin and / or carboxyl super-weather-resistant polyester resin, the hydroxyl value range of the hydroxyl super-weather-resistant polyester resin is 5-25 mgKOH / g, the hydroxyl value range of the carboxyl super-weather-resistant polyester resin is 5-25 mgKOH / g, and the hydroxyl value range of the carboxyl super-weather-resistant polyester resin is 5-25 mgKOH / g. The acid value range of the carboxyl super-weather-resistant polyester resin is 5-15 mgKOH / g; the thermosetting resin B is modified weather-proof polyester resin. The liquid coating provided by the invention has the advantages of good flexibility, light weight, low cost and the like. When being applied to a photovoltaic module, the coating has excellent impact resistance, ultraviolet aging resistance and thermal cycling aging resistance, and is high in visible light transmittance and excellent in binding power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic packaging materials, and in particular to a liquid coating and a preparation method and application thereof. Background Art

[0002] The packaging materials in the photovoltaic field are required to have anti-ultraviolet and anti-aging properties. The laminated structure of the existing typical photovoltaic module is formed by laminating ultra-white tempered embossed glass, the first EVA film, the solar cell string, the second EVA film and the back plate in sequence, wherein: the ultra-white tempered embossed glass weighs up to 8 kg per square meter. The photovoltaic module assembled by the laminated structure of the photovoltaic module is usually of large mass. When it is used in occasions such as the top or wall of a building, it puts forward higher requirements on the supporting structure of the photovoltaic module, increases the difficulty of engineering construction and the cost of installation. At the same time, the packaging structure of the existing photovoltaic module has a single appearance and is not easy to change to meet the aesthetic requirements of different buildings.

[0003] Currently, there are some technical solutions to the problem of lightweighting photovoltaic modules, that is, using high-transmittance films and transparent backplanes to replace tempered glass. However, in actual applications, since these high-transmittance films and transparent backplanes mostly only use EVA, POE and other adhesive films, the photovoltaic modules packaged in this way cannot meet the technical standards of the photovoltaic industry in terms of impact resistance, fire resistance and other properties.

[0004] Patent No. CN102610680A discloses a solar cell backplane with UV-cured weather-resistant coating, but the liquid coating process it adopts is relatively complicated, with a high defect rate and large equipment investment. For example, a series of Chinese invention patents with publication No. CN102712184A, CN103346182A, CN102969382B, CN101290950B, CN103958196A, etc. all use fluorinated polymers, but fluorinated polymers are expensive, which increases production costs. Moreover, the above patents disclose only materials for photovoltaic backplanes, which are opaque, low in hardness and weak in rigidity, and are not suitable for replacing existing tempered glass.

[0005] The patent with publication number CN105637653A discloses a photovoltaic panel and a method for manufacturing the photovoltaic panel. Specifically, plastic based on epoxy group-containing acrylate and reinforced with glass fiber is used as the packaging material for the front light side and the back light side of the solar cell string. Although this method solves the problem of heavy weight of the packaging material of the laminated structure of the photovoltaic module, it uses all expensive acrylate as the packaging material, which is not only costly, but also causes the photovoltaic module to have a single color. This technology also has the problems of high lamination temperature and high energy consumption during the lamination process, and the obtained laminated structure of the photovoltaic module is curved, has a certain curvature, and is uneven, which is not conducive to the installation and implementation of the photovoltaic module and affects the appearance.

[0006] The patent with publication number CN115230263A discloses an integrated glass fiber reinforced photovoltaic panel and its preparation method and application. The limitation lies in the molding process of polyester material: the production efficiency is low and the required polyester material is a solvent-free product.

[0007] The patent with publication number CN108022988B discloses a laminated structure of a photovoltaic module and a preparation method thereof, and a photovoltaic module. The specific method adopted is: a first encapsulation layer (powder coating + glass fiber), a second encapsulation layer (powder coating + glass fiber), the powder coating is acrylic resin / super weather-resistant polyester, and its structure is: fluoroplastic film layer / first encapsulation layer / second encapsulation layer, using screw extrusion process, multi-layer coating, hot pressing bonding, slitting and other processes, the process is complicated and the efficiency is low. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a flexible, lightweight, low-cost liquid coating and a preparation method and application thereof.

[0009] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:

[0010] In one aspect, the present invention provides a liquid coating, wherein the raw materials for preparing the liquid coating include a thermosetting resin A, a thermosetting resin B and a curing agent, wherein:

[0011] The thermosetting resin A is a hydroxyl super weather-resistant polyester resin and / or a carboxyl super weather-resistant polyester resin, the hydroxyl value of the hydroxyl super weather-resistant polyester resin is in the range of 5 to 25 mgKOH / g, and the acid value of the carboxyl super weather-resistant polyester resin is in the range of 5 to 15 mgKOH / g;

[0012] The thermosetting resin B is a modified weather-resistant polyester resin.

[0013] Preferably, the modified weather-resistant polyester resin has a hydroxyl value in the range of 5 to 10 mgKOH / g and an acid value in the range of 5 to 10 mgKOH / g.

[0014] Preferably, the weight proportion of the thermosetting resin A is 50 to 100 parts, preferably 50 to 98 parts, and more preferably 50 to 95 parts.

[0015] Preferably, the weight proportion of the thermosetting resin B is 20 to 50 parts, preferably 25 to 45 parts.

[0016] Preferably, the modified weather-resistant polyester resin is a polyester resin modified with malonic acid or a malonic acid derivative and / or an epoxy-modified polyester resin. Further preferably, the malonic acid derivative is selected from one or more of dimethyl malonate, diethyl malonate and monomethyl malonate.

[0017] Preferably, the thermosetting resin A is a copolyester resin obtained by the reaction of a dibasic acid and a diol.

[0018] Preferably, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, cyclohexanedicarboxylic acid, adipic acid and sebacic acid.

[0019] Preferably, the diol is selected from one or more of ethylene glycol, propylene glycol, neopentyl glycol, cyclohexanedimethanol and hexanediol.

[0020] Preferably, the molar ratio of the dibasic acid to the diol is 1:1.3 to 2; more preferably, it is 1:1.4 to 1.7.

[0021] Preferably, the thermosetting resin A is selected from one or more of thermosetting resin A1, thermosetting resin A2 and thermosetting resin A3.

[0022] Preferably, in the preparation of the raw material of the thermosetting resin A1, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid and adipic acid, and the diol is selected from ethylene glycol and / or neopentyl glycol.

[0023] Preferably, in the preparation of the raw material of the thermosetting resin A2, the dibasic acid is selected from one or more of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexylene glycol and / or neopentyl glycol.

[0024] Preferably, in the preparation of the raw material of the thermosetting resin A3, the dibasic acid is selected from one of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexylene glycol and / or cyclohexanedimethanol.

[0025] Preferably, the glass transition temperature of the thermosetting resin A1 is in the range of 55 to 75°C, more preferably in the range of 56 to 75°C, and even more preferably in the range of 60 to 75°C.

[0026] Preferably, the relative molecular weight of the thermosetting resin A1 is in the range of 15000 to 20000; more preferably, in the range of 15500 to 19000; and even more preferably, in the range of 16500 to 19000.

[0027] Preferably, the weight proportion of the thermosetting resin A1 is 30 to 55 parts, preferably 35 to 55 parts.

[0028] Preferably, the glass transition temperature of the thermosetting resin A2 is in the range of 25 to 45°C, more preferably in the range of 26 to 45°C, and even more preferably in the range of 30 to 45°C.

[0029] Preferably, the relative molecular weight of the thermosetting resin A2 is in the range of 5000-10000; more preferably, it is in the range of 6000-10000; and even more preferably, it is in the range of 8000-10000.

[0030] Preferably, the weight proportion of the thermosetting resin A2 is 15 to 30 parts, preferably 15 to 25 parts.

[0031] Preferably, the glass transition temperature of the thermosetting resin A3 is in the range of -10 to 10°C, more preferably in the range of -8 to 10°C, and even more preferably in the range of -5 to 10°C.

[0032] Preferably, the relative molecular weight of the thermosetting resin A3 is in the range of 15000-40000; more preferably, it is in the range of 18000-30000; and even more preferably, it is in the range of 19000-25000.

[0033] Preferably, the weight proportion of the thermosetting resin A3 is 5 to 15 parts, preferably 6 to 15 parts.

[0034] Preferably, the curing agent includes curing agent 1 and curing agent 2, wherein the curing agent 1 is an isocyanate curing agent, preferably one or more of blocked isocyanate and open isocyanate, and further preferably one or more of Dornaide TMA-100, TLA-100, TUL-100, TKA-75S, and TPA-B80X.

[0035] Preferably, the added amount of the curing agent 1 is 5-10% of the mass of the thermosetting resin A, preferably 5-9%, and more preferably 6-8%.

[0036] The curing agent 2 is selected from one or more monomers or modified monomers and anhydride curing agents that can utilize Michael addition reaction to undergo curing reaction; further preferably, the curing agent 2 is selected from one or more of triglycidyl isocyanurate, triglycidyl trimellitate, diglycidyl terephthalate, glycidyl methacrylate, hydroxyalkylamide, methylhexahydrophthalic anhydride, phthalic anhydride, trimellitic anhydride and tetrahydrophthalic anhydride; further preferably, glycidyl methacrylate and / or methylhexahydrophthalic anhydride.

[0037] Preferably, the added amount of the curing agent 2 is 5-15% of the mass of the thermosetting resin B, preferably 6-12%, and more preferably 8-12%.

[0038] Preferably, the raw materials for preparing the liquid coating further include an organic solvent, an auxiliary agent and an accelerator.

[0039] Preferably, the organic solvent is selected from one or more of butanone, ethyl acetate and methyl acetate; more preferably, it is one of butanone, ethyl acetate and methyl acetate.

[0040] Preferably, the weight proportion of the organic solvent is 50 to 100 parts, preferably 60 to 100 parts, more preferably 60 to 90 parts, and even more preferably 60 to 80 parts.

[0041] Preferably, the auxiliary agent is selected from one or more of UV absorbers, UV stabilizers, defoamers, leveling agents, catalysts, anti-hydrolysis agents, and antioxidants.

[0042] Preferably, the weight proportion of the auxiliary agent is 5 to 10 parts, preferably 5 to 8 parts, and more preferably 5 to 7 parts.

[0043] Preferably, the accelerator is one or more of a tertiary amine accelerator or an epoxy resin curing accelerator.

[0044] Preferably, the weight proportion of the accelerator is 0.1 to 0.5 parts, preferably 0.1 to 0.4 parts, and more preferably 0.1 to 0.3 parts.

[0045] In a second aspect, the present invention provides a method for preparing the liquid coating as described in any one of the above, comprising the following steps:

[0046] Thermosetting resin A, thermosetting resin B, organic solvent, auxiliary agent, curing agent and accelerator are mixed uniformly to obtain the liquid coating.

[0047] In a third aspect, the present invention provides a use of the liquid coating described in any one of the above items in the preparation of a photovoltaic module.

[0048] In a fourth aspect, the present invention provides a method for preparing a photovoltaic module comprising the liquid coating described in any one of the above, comprising the following steps:

[0049] (1) mixing thermosetting resin A, thermosetting resin B, organic solvent, additive, curing agent and accelerator in proportion to obtain a desired liquid coating;

[0050] (2) evenly coating the liquid coating obtained in step (1) on the glass fiber composite board and baking to obtain the glass fiber composite board;

[0051] (3) stacking the glass fiber composite board obtained in step (2), the first adhesive film layer, the battery string layer, the second adhesive film layer and the back plate layer in sequence from top to bottom and laminating them;

[0052] (4) Post-curing the photovoltaic module laminated in step (3) to obtain the photovoltaic module.

[0053] Preferably, in step (2), the baking is carried out at 80-100° C. for 1.5-5 min, preferably at 85-100° C. for 1.5-5 min.

[0054] Preferably, in step (3), the lamination process includes a first heating stage, a second heating stage and a third pressurized cooling stage.

[0055] Preferably, the heating temperature in the first heating stage is 80-110°C, preferably 80-100°C, and more preferably 80-90°C.

[0056] Preferably, the heating time of the first heating stage is 50 to 100 s, preferably 50 to 90 s, more preferably 50 to 80 s, and even more preferably 60 to 80 s.

[0057] Preferably, the heating temperature in the second heating stage is 110-140°C, preferably 110-130°C, and more preferably 110-125°C.

[0058] Preferably, the heating time of the second heating stage is 100 to 200 s, preferably 100 to 180 s, more preferably 100 to 150 s, and even more preferably 100 to 140 s.

[0059] Preferably, the temperature in the third pressurized cooling stage is controlled to be 10-50°C, preferably 20-50°C, and more preferably 30-50°C.

[0060] Preferably, the time of the third pressurized cooling stage is controlled to be 30 to 60 seconds, preferably 35 to 60 seconds, more preferably 40 to 60 seconds, and even more preferably 45 to 60 seconds.

[0061] Preferably, the pressure in the third pressurized cooling stage is controlled to be 0.05 to 0.25 MPa, preferably 0.1 to 0.25 MPa, and more preferably 0.15 to 0.25 MPa.

[0062] Preferably, in step (4), the post-curing temperature is controlled to be 90 to 120°C, preferably 90 to 110°C, and more preferably 100 to 110°C.

[0063] Preferably, in step (4), the post-curing time is controlled to be at least 30 minutes, preferably 30 to 60 minutes.

[0064] In a fifth aspect, the present invention provides a photovoltaic module obtained according to the above preparation method.

[0065] Compared with the prior art, the technical effects of the present invention are:

[0066] Compared with conventional glass fiber reinforced layer coatings, the present invention increases its flexibility by optimizing the raw material components for preparing the liquid coating. The liquid coating provided by the present invention can fully infiltrate the glass fiber composite board, and the degree of curing and cross-linking is higher. The bonding force between the two is strong and it is not easy to fall off. At the same time, the obtained glass fiber reinforced layer is colorless and transparent, which enhances its light transmittance. The present invention also provides a method for applying the coating to photovoltaic panels. By adopting a multiple curing system and optimizing the lamination process, the coating is not anti-sticky, and the roll-to-roll batch industrial production of the coating method is realized. At the same time, it also has the advantages of short time, simple process, and safer process conditions. The present invention reduces the cost of photovoltaic modules from both material and process aspects and improves production efficiency. DETAILED DESCRIPTION

[0067] In order to make the technical solutions and beneficial effects of the present invention more clearly understood, the following is a detailed description by listing specific embodiments. Unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application belongs.

[0068] If no specific techniques or conditions are specified in the following examples, they are generally carried out according to conventional techniques or conditions described in the literature in the art, or according to the product instructions and the conditions recommended by the manufacturer.

[0069] Unless otherwise indicated, various starting materials, materials and reagents were either commercially available or synthesized according to known methods.

[0070] The first aspect of the present invention provides a liquid coating, wherein the raw materials for preparing the liquid coating include a thermosetting resin A, a thermosetting resin B and a curing agent, wherein:

[0071] The thermosetting resin A is a hydroxyl super weather-resistant polyester resin and / or a carboxyl super weather-resistant polyester resin, the hydroxyl value of the hydroxyl super weather-resistant polyester resin is in the range of 5 to 25 mgKOH / g, and the acid value of the carboxyl super weather-resistant polyester resin is in the range of 5 to 15 mgKOH / g;

[0072] The thermosetting resin B is a modified weather-resistant polyester resin.

[0073] In a preferred example, the hydroxyl value range of the hydroxyl super weather resistant polyester resin is 5 to 10 mgKOH / g, specifically preferably 5 mgKOH / g, 6 mgKOH / g, 7 mgKOH / g, 8 mgKOH / g, 9 mgKOH / g, and 10 mgKOH / g, and the acid value range is 5 to 10 mgKOH / g, specifically preferably 5 mgKOH / g, 6 mgKOH / g, 7 mgKOH / g, 8 mgKOH / g, 9 mgKOH / g, and 10 mgKOH / g.

[0074] In a preferred example, the weight proportion of the thermosetting resin A is 50 to 100 parts.

[0075] In a preferred example, the weight percentage of the thermosetting resin A is 50 to 98 parts.

[0076] In a preferred example, the weight proportion of the thermosetting resin A is 50 to 95 parts, and specifically preferably 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, etc.

[0077] In a preferred example, the weight proportion of the thermosetting resin B is 20 to 50 parts.

[0078] In a preferred example, the weight proportion of the thermosetting resin B is 25 to 45 parts, and specifically preferably 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, etc.

[0079] In a preferred example, the modified weather-resistant polyester resin is a polyester resin modified with malonic acid or a malonic acid derivative and / or an epoxy-modified polyester resin.

[0080] In a preferred example, the malonic acid derivative is selected from one or more of dimethyl malonate, diethyl malonate and monomethyl malonate.

[0081] In a preferred example, the thermosetting resin A is a copolyester resin obtained by the reaction of a dibasic acid and a diol.

[0082] In a specific embodiment, the present invention provides a method for preparing thermosetting resin A.

[0083] Specifically, (1) a dibasic acid, a diol, and a catalyst are added to a reactor in a certain ratio, stirred, and the reaction system is heated to perform an esterification reaction to obtain an intermediate product;

[0084] (2) The intermediate product obtained in step (1) is subjected to a condensation polymerization reaction to obtain a thermosetting resin A.

[0085] In a preferred example, in the raw materials for preparing the thermosetting resin A, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, cyclohexanedicarboxylic acid, adipic acid and sebacic acid.

[0086] In a preferred example, in the raw materials for preparing the thermosetting resin A, the diol is selected from one or more of ethylene glycol, propylene glycol, neopentyl glycol, cyclohexanedimethanol and hexanediol.

[0087] In a preferred example, the molar ratio of the dibasic acid to the diol is 1:1-2.

[0088] In a preferred example, the molar ratio of the dibasic acid to the diol is 1:1.2-1.6, and specifically preferably 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.55, etc.

[0089] In a preferred example, the temperature increase in step (1) includes a first temperature increase, a second temperature increase, and a third temperature increase.

[0090] In a preferred example, the first temperature is controlled to be raised to 180-200°C for reaction for 0.4-0.6h, the second temperature is controlled to be raised to 215-220°C for insulation for 1-1.5h, and the third temperature is controlled to be raised to 220-240°C for reaction for 2-3h.

[0091] In a preferred example, the end point of the esterification reaction is an esterification rate > 95%.

[0092] In a preferred example, the temperature of the polycondensation reaction is controlled to be 250-275°C.

[0093] In a preferred example, the temperature of the polycondensation reaction is controlled to be 250-260°C.

[0094] In a preferred example, the pressure of the polycondensation reaction is controlled to be below 100 Pa.

[0095] In a preferred example, the present invention provides a method for preparing thermosetting resin B, which is the same as the method for preparing thermosetting resin A, except that the raw materials are different.

[0096] Specifically, in the raw materials for preparing the thermosetting resin B, the dibasic acid is selected from phthalic acid and / or isophthalic acid, the diol is selected from neopentyl glycol, and ethylene glycol diglycidyl ether is also included.

[0097] In a preferred example, the thermosetting resin A is selected from one or more of thermosetting resin A1, thermosetting resin A2 and thermosetting resin A3.

[0098] In a preferred example, the thermosetting resin A is selected from a mixture of thermosetting resin A1, thermosetting resin A2 and thermosetting resin A3.

[0099] In a preferred example, the weight proportion of the thermosetting resin A1 is 30 to 55 parts, preferably 35 to 55 parts, and specifically preferably 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 parts, etc.

[0100] In a preferred example, the weight proportion of the thermosetting resin A2 is 15 to 30 parts, preferably 15 to 25 parts, and specifically preferably 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, etc.

[0101] In a preferred example, the weight proportion of the thermosetting resin A3 is 5 to 15 parts, preferably 6 to 15 parts, and specifically preferably 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, and 15 parts.

[0102] In a preferred example, in preparing the raw material of the thermosetting resin A1, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid and adipic acid, and the diol is selected from ethylene glycol and / or neopentyl glycol.

[0103] In a preferred example, in the preparation of the thermosetting resin A1 raw material, based on the molar content of the dibasic acid being 100%, the molar content of the terephthalic acid is 50-60% (specifically preferably 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc.), the molar content of the isophthalic acid is 35-45% (specifically preferably 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc.), and the molar content of the adipic acid is 0-15% (specifically preferably 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, etc.).

[0104] In a preferred example, the molar content of the terephthalic acid is 51-60%, the molar content of the isophthalic acid is 35-42%, and the molar content of the adipic acid is 0-13%.

[0105] In a preferred example, in the preparation of the thermosetting resin A1 raw material, based on the molar content of the diol being 100%, the molar content of the ethylene glycol is 50-60% (specifically preferably 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc.), and the molar content of the neopentyl glycol is 40-50% (specifically preferably 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, etc.).

[0106] In a preferred example, the molar content of the ethylene glycol is 55-60%, and the molar content of the neopentyl glycol is 40-45%.

[0107] In a preferred example, the glass transition temperature of the thermosetting resin A1 is in the range of 55-75°C.

[0108] In a preferred example, the glass transition temperature of the thermosetting resin A1 is in the range of 56-75°C.

[0109] In a specific and preferred example, the glass transition temperature range of the thermosetting resin A1 is 60-75°C, and specifically preferably 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, etc.

[0110] In a preferred example, the relative molecular weight of the thermosetting resin A1 is in the range of 15,000 to 20,000.

[0111] In a preferred example, the relative molecular weight of the thermosetting resin A1 is in the range of 15500 to 19000.

[0112] In a specific and preferred example, the relative molecular weight range of the thermosetting resin A1 is 16500-19000, and specifically preferably 17000, 17100, 17200, 17300, 17400, 17500, 17600, 17700, 17800, 18000, 18200, 18400, 18600, and 18800.

[0113] In a preferred example, in preparing the raw material of the thermosetting resin A2, the dibasic acid is selected from one or more of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexylene glycol and / or neopentyl glycol.

[0114] In a preferred example, in the preparation of the thermosetting resin A2 raw material, based on the molar content of the dibasic acid being 100%, the molar content of the terephthalic acid is 30-45% (specifically preferably 32%, 34%, 36%, 38%, 40%, 42%, etc.), the molar content of the cyclohexanedicarboxylic acid is 15-30% (specifically preferably 16%, 18%, 20%, 22%, 24%, 26%, 28%, etc.), and the molar content of the sebacic acid is 38-55% (specifically preferably 40%, 42%, 44%, 46%, 48%, 50%, 52%, etc.).

[0115] In a preferred example, the molar content of the terephthalic acid is 32-43%, the molar content of the cyclohexanedicarboxylic acid is 15-28%, and the molar content of the sebacic acid is 39-52%.

[0116] In a preferred example, in the preparation of the thermosetting resin A2 raw material, based on the molar content of the diol being 100%, the molar content of the hexanediol is 30-40% (specifically preferably 32%, 34%, 36%, 38%, etc.), and the molar content of the neopentyl glycol is 60-70% (specifically preferably 62%, 64%, 66%, 68%, etc.).

[0117] In a preferred example, the molar content of the hexylene glycol is 30-38%, and the molar content of the neopentyl glycol is 62-70%.

[0118] In a preferred example, the glass transition temperature of the thermosetting resin A2 is in the range of 25 to 45°C.

[0119] In a preferred example, the glass transition temperature of the thermosetting resin A2 is in the range of 26 to 45°C.

[0120] In a preferred example, the glass transition temperature range of the thermosetting resin A2 is 30-45°C, and specifically preferably 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, etc.

[0121] In a preferred example, the relative molecular weight of the thermosetting resin A2 is in the range of 5000-10000.

[0122] In a preferred example, the relative molecular weight of the thermosetting resin A2 is in the range of 6000 to 10000.

[0123] In a preferred example, the relative molecular weight of the thermosetting resin A2 is in the range of 8000 to 10000, and is preferably 8200, 8400, 8600, 8800, 9000, 9200, 9400, 9600, 9800, etc.

[0124] In a preferred example, in preparing the raw material of the thermosetting resin A3, the dibasic acid is selected from one of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexylene glycol and / or cyclohexanedimethanol.

[0125] In a preferred example, in the preparation of the thermosetting resin A3 raw material, based on the molar content of the dibasic acid being 100%, the molar content of the terephthalic acid is 40-65% (specifically preferably 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, etc.), the molar content of the cyclohexanedicarboxylic acid is 25-45% (specifically preferably 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, etc.), and the molar content of the sebacic acid is 10-20% (specifically preferably 12%, 14%, 16%, 18%, etc.).

[0126] In a preferred example, the molar content of the terephthalic acid is 40-64%, the molar content of the cyclohexanedicarboxylic acid is 26-45%, and the molar content of the sebacic acid is 10-18%.

[0127] In a preferred example, in the preparation of the thermosetting resin A3 raw material, based on the molar content of the diol being 100%, the molar content of the cyclohexanedimethanol is 30-50% (specifically preferably 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, etc.), and the molar content of the hexanediol is 50-70% (specifically preferably 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, etc.).

[0128] In a preferred example, the molar content of the cyclohexanedimethanol is 35-45%, and the molar content of the hexanediol is 55-65%.

[0129] In a preferred example, the glass transition temperature of the thermosetting resin A3 is in the range of -10 to 10°C.

[0130] In a preferred example, the glass transition temperature of the thermosetting resin A3 is in the range of -8 to 10°C.

[0131] In a preferred example, the glass transition temperature range of the thermosetting resin A3 is -5 to 10°C, and specifically preferably -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, etc.

[0132] In a preferred example, the relative molecular weight of the thermosetting resin A3 is in the range of 15000-40000.

[0133] In a preferred example, the relative molecular weight of the thermosetting resin A3 is in the range of 18,000 to 30,000.

[0134] In a preferred example, the relative molecular weight of the thermosetting resin A3 is in the range of 19,000 to 25,000.

[0135] In a specific and preferred example, the relative molecular weight range of the thermosetting resin A3 is 19000-22000, and specifically preferably 19200, 19400, 19600, 19800, 20000, 20100, 20200, 20300, 20400, 20500, 21000, 21200, 21400, 21600, 21800, etc.

[0136] In a preferred example, the curing agent includes curing agent 1 and curing agent 2, wherein the curing agent 1 is an isocyanate curing agent.

[0137] In a preferred example, the curing agent 1 is one or more of blocked isocyanate and open isocyanate.

[0138] In a preferred example, the curing agent 1 is one or more of TMA-100, TLA-100, TUL-100, TKA-75S, and TPA-B80X.

[0139] In a preferred example, the added amount of the curing agent 1 is 5-10% of the mass of the thermosetting resin A.

[0140] In a preferred example, the added amount of the curing agent 1 is 5-9% of the mass of the thermosetting resin A.

[0141] In a preferred example, the added amount of the curing agent 1 is 6-8% of the mass of the thermosetting resin A, and specifically preferably 6.2%, 6.4%, 6.6%, 6.8%, 7%, 7.2%, 7.4%, 7.6%, 7.8%, etc.

[0142] In a preferred example, the curing agent 2 is selected from one or more monomers or modified monomers that can undergo a curing reaction by Michael addition reaction and acid anhydride curing agents.

[0143] In the present invention, if the thermosetting resin B is a polyester resin modified by malonic acid or a malonic acid derivative, it can be cured and crosslinked with a monomer (such as GMA) or a modified monomer that can be cured by Michael addition reaction. In another preferred embodiment, if the thermosetting resin B is an epoxy-modified polyester resin, it can be cured and crosslinked with an acid anhydride.

[0144] In a preferred example, the curing agent 2 is selected from one or more of triglycidyl isocyanurate, triglycidyl trimellitate, diglycidyl terephthalate, glycidyl methacrylate, hydroxyalkylamide, methylhexahydrophthalic anhydride, phthalic anhydride, trimellitic anhydride and tetrahydrophthalic anhydride.

[0145] In a preferred example, the curing agent 2 is selected from glycidyl methacrylate and / or methyl hexahydrophthalic anhydride.

[0146] In a preferred example, the added amount of the curing agent 2 is 5-15% of the mass of the thermosetting resin B.

[0147] In a preferred example, the added amount of the curing agent 2 is 6-12% of the mass of the thermosetting resin B.

[0148] In a preferred example, the added amount of the curing agent 2 is 8-12% of the mass of the thermosetting resin B, and specifically preferably 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11.0%, 11.5%, etc.

[0149] In a preferred example, the raw materials for preparing the liquid coating further include an organic solvent, an auxiliary agent and an accelerator.

[0150] In the present invention, both the thermosetting resin A and the thermosetting resin B can be completely dissolved in the organic solvent.

[0151] In the present invention, the selected organic solvent is an organic solvent with a low boiling point.

[0152] In a preferred example, the organic solvent is selected from one or more of butanone, ethyl acetate and methyl acetate.

[0153] In a preferred example, the organic solvent is selected from one of butanone, ethyl acetate and methyl acetate. In the present invention, a single-component solvent is selected, and the solvent can be reused, thereby further reducing costs.

[0154] In a preferred example, the weight proportion of the organic solvent is 50 to 100 parts.

[0155] In a preferred example, the weight proportion of the organic solvent is 60 to 100 parts.

[0156] In a preferred example, the weight proportion of the organic solvent is 60 to 90 parts.

[0157] In a preferred example, the weight proportion of the organic solvent is 60 to 80 parts, and specifically preferably 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, etc.

[0158] In a preferred example, the auxiliary agent is selected from one or more of a UV absorber, a UV stabilizer, a defoamer, a leveling agent, a catalyst, an anti-hydrolysis agent, and an antioxidant.

[0159] In a preferred example, the weight proportion of the auxiliary agent is 5 to 10 parts.

[0160] In a preferred example, the weight proportion of the auxiliary agent is 5 to 8 parts.

[0161] In a preferred example, the weight proportion of the auxiliary agent is 5 to 7 parts, and specifically preferably 5.5 parts, 6 parts, 6.5 parts, etc.

[0162] In the present invention, the ultraviolet absorber, ultraviolet stabilizer, defoamer, leveling agent, catalyst, anti-hydrolysis agent, and antioxidant can all be selected according to common knowledge, and this application does not make any sole limitation thereto.

[0163] In a preferred example, the accelerator is one or more of a tertiary amine accelerator or an epoxy resin curing accelerator.

[0164] In a preferred example, the weight portion of the accelerator is 0.1 to 0.5 parts.

[0165] In a preferred example, the weight portion of the accelerator is 0.1 to 0.4 parts.

[0166] In a preferred example, the weight portion of the accelerator is 0.1 to 0.3 parts, and specifically preferably 0.15 parts, 0.20 parts, 0.25 parts, etc. The liquid coating provided by the present invention is applicable to the process of the flexible battery core layer.

[0167] In a second aspect, the present invention provides a method for preparing the liquid coating as described in any one of the above, comprising the following steps:

[0168] Thermosetting resin A, thermosetting resin B, organic solvent, auxiliary agent, curing agent and accelerator are mixed uniformly to obtain the liquid coating.

[0169] In a third aspect, the present invention provides a use of the liquid coating described in any one of the above items in the preparation of a photovoltaic module.

[0170] In a fourth aspect, the present invention provides a method for preparing a photovoltaic module comprising the liquid coating described in any one of the above, comprising the following steps:

[0171] (1) mixing thermosetting resin A, thermosetting resin B, organic solvent, additive, curing agent and accelerator in proportion to obtain a desired liquid coating;

[0172] (2) evenly coating the liquid coating obtained in step (1) on the glass fiber composite board and baking to obtain the glass fiber composite board;

[0173] (3) stacking the glass fiber composite board obtained in step (2), the first adhesive film layer, the battery string layer, the second adhesive film layer and the back plate layer in sequence from top to bottom and laminating them;

[0174] (4) Post-curing the photovoltaic module laminated in step (3) to obtain the photovoltaic module.

[0175] In the present invention, the baking temperature is determined according to the boiling point of the organic solvent in the liquid coating of the present invention.

[0176] In a preferred example, in step (2), the baking is performed at 80-100° C. for 1.5-5 min.

[0177] In a preferred example, in step (2), the baking is carried out at 85-100°C for 1.5-5 minutes. In this step (i.e., the pre-curing stage), the reaction conditions of the thermosetting resin and the curing agent are designed so that a reaction occurs during the coating and drying process, thereby having a certain degree of cross-linking and curing. The purpose is to ensure that the resin can fully infiltrate the glass fiber layer at a lower degree of curing and cross-linking, so that there are no defects such as bubbles in the coating, and at the same time, the coating surface is not sticky, and there is no need to apply a release layer when winding online.

[0178] In a preferred example, in step (3), the lamination process includes a first heating stage, a second heating stage and a third pressurized cooling stage.

[0179] In a preferred example, the heating temperature in the first heating stage is 80-110°C.

[0180] In a preferred example, the heating temperature in the first heating stage is 80-100°C.

[0181] In a preferred example, the heating temperature of the first heating stage is 80-90°C, specifically 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, etc.

[0182] In a preferred example, the heating time of the first heating stage is 50 to 100 seconds.

[0183] In a preferred example, the heating time of the first heating stage is 50 to 90 seconds.

[0184] In a preferred example, the heating time of the first heating stage is 50 to 80 seconds.

[0185] In a preferred example, the heating time of the first heating stage is 60 to 80 seconds, and specifically preferably 62 seconds, 64 seconds, 68 seconds, 70 seconds, 72 seconds, 74 seconds, 76 seconds, 78 seconds, etc.

[0186] In a preferred example, the heating temperature in the second heating stage is 110-140°C.

[0187] In a preferred example, the heating temperature in the second heating stage is 110-130°C.

[0188] In a preferred example, the heating temperature in the second heating stage is 110-125°C, and specifically preferably 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, etc.

[0189] In a preferred example, the heating time of the second heating stage is 100-200 seconds.

[0190] In a preferred example, the heating time of the second heating stage is 100 to 180 seconds.

[0191] In a preferred example, the heating time of the second heating stage is 100-150 seconds.

[0192] In a preferred example, the heating time of the second heating stage is 100-140 seconds.

[0193] In a preferred example, the heating time of the second heating stage is 100-120 s, and specifically preferably 102 s, 104 s, 106 s, 108 s, 110 s, 112 s, 114 s, 116 s, 118 s, etc.

[0194] In a preferred example, the temperature of the third pressurized cooling stage is controlled to be 10-50°C.

[0195] In a preferred example, the temperature of the third pressurized cooling stage is controlled to be 20-50°C.

[0196] In a preferred example, the temperature of the third pressurized cooling stage is controlled to be 30-50°C, and specifically preferably 32°C, 34°C, 36°C, 40°C, 42°C, 44°C, 46°C, 48°C, etc.

[0197] In a preferred example, the time of the third pressurized cooling stage is controlled to be 30 to 60 seconds.

[0198] In a preferred example, the time of the third pressurized cooling stage is controlled to be 35 to 60 seconds.

[0199] In a preferred example, the time of the third pressurized cooling stage is controlled to be 40 to 60 seconds.

[0200] In a preferred example, the time of the third pressurized cooling stage is controlled to be 45 to 60 seconds, and specifically preferably 46 seconds, 48 ​​seconds, 50 seconds, 52 seconds, 54 seconds, 56 seconds, 58 seconds, etc.

[0201] In a preferred example, the pressure in the third pressurized cooling stage is controlled to be 0.05-0.25 MPa.

[0202] In a preferred example, the pressure in the third pressurized cooling stage is controlled to be 0.1-0.25 MPa.

[0203] In a preferred example, the pressure in the third pressurized cooling stage is controlled to be 0.15-0.25 MPa, and specifically preferably 0.16 MPa, 0.18 MPa, 0.20 MPa, 0.22 MPa, 0.24 MPa, etc.

[0204] Compared with the existing lamination process with temperature requirements of 140-180°C and lamination time of 10-20 minutes, the lamination process provided by the present invention requires lower temperature, shorter time, and simpler process, making the laminated parts smoother, without appearance defects such as warping, and improving the yield rate.

[0205] In a preferred example, in step (4), the temperature of the post-curing is controlled to be 90-120°C.

[0206] In a preferred example, in step (4), the post-curing temperature is controlled to be 90-110°C.

[0207] In a preferred example, in step (4), the post-curing temperature is controlled to be 100-110°C, and specifically preferably 102°C, 104°C, 106°C, 108°C, etc.

[0208] In a preferred example, in step (4), the post-curing time is controlled to be at least 30 minutes.

[0209] In a preferred example, in step (4), the post-curing time is controlled to be 30 to 60 minutes, and more preferably 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, etc. The post-curing treatment step of the present invention is carried out in a curing room and does not occupy a production line.

[0210] In the method for preparing photovoltaic modules, in the pre-curing stage (i.e., step 2), the thermosetting resin B reacts rapidly with the curing agent 2 and the accelerator under appropriate baking conditions to form a high degree of curing cross-linking; while the thermosetting resins A1, A2, and A3 cannot react with the curing agent 2 due to different reaction mechanisms, and under the above-mentioned baking conditions, the reaction degree of the thermosetting resins A1, A2, and A3 with the curing agent 1 is low (the reaction degree is less than 15% through the gel test); in the hot pressing molding stage (i.e., step 3), they are fully bonded with the first adhesive film layer and the second adhesive film layer; finally, under appropriate process conditions in the post-curing stage, the thermosetting resins A1, A2, and A3 react fully with the curing agent 1 to form a sufficient degree of curing cross-linking.

[0211] In the present invention, the material of the first adhesive film layer and the second adhesive film layer can be any known adhesive film material, for example, EVA adhesive film, POE adhesive film, etc. can be specifically used.

[0212] In the present invention, the battery string layer may include crystalline silicon battery cells, or amorphous silicon battery cells, or any type of thin film battery cells, and the present application does not impose any particular limitation on them during implementation.

[0213] In a fifth aspect, the present invention provides a photovoltaic module obtained according to the above preparation method.

[0214] The present invention optimizes the coating components and process conditions so that the prepared glass fiber composite board is colorless and transparent with high light transmittance. The prepared photovoltaic front panel composite material has the advantages of no anti-sticking, easy winding, light weight, etc. while meeting the technical standards of the photovoltaic industry such as UV resistance, aging resistance, impact resistance, and fire resistance. The coating method is realized in a roll-to-roll batch industrial continuous production, with low cost and improved production efficiency.

[0215] Example 1

[0216] The preparation method of thermosetting resin A1 is as follows:

[0217] The acid components of terephthalic acid (TPA), isophthalic acid (IPA), adipic acid (AA), alcohol components of ethylene glycol (EG), neopentyl glycol (NPG), and 100ppm of zinc acetate were put into a 2L stainless steel reactor, stirred at 50rpm under nitrogen protection, and quickly heated to 180-200℃ for 0.5 hours, then gradually heated to 220℃ for 1.2 hours, and then heated to 220-240℃ for 2.5 hours. When the esterification rate is >95%, the reaction is terminated. Then 30ppm of tetrabutyl titanate and 60ppm of triphenyl phosphate are added, the temperature is continued to rise and the pressure is slowly reduced, the speed is adjusted to 40rpm, the temperature is controlled to between 250 and 275℃, and the pressure is gradually reduced to below 100Pa for polycondensation reaction. Sampling and analysis were performed. When the polymer viscosity reached 0.7-1.1 dl / g, stirring was stopped, vacuum was eliminated, and the product was discharged to obtain thermosetting resin A1. According to the above preparation method, samples 1-4 were prepared according to different molar ratios of raw materials. The specific feeding information and product indicators are shown in Table 1.

[0218] Table 1

[0219]

[0220] The preparation method of thermosetting resin A2 is as follows:

[0221] The acid components of terephthalic acid (TPA), 1,4-cyclohexanedicarboxylic acid (CHDA), sebacic acid (SA), the alcohol components of neopentyl glycol (NPG), hexylene glycol (HD), and 100ppm of zinc acetate were put into a 2L stainless steel reactor, stirred at 50rpm under nitrogen protection, and quickly heated to 180-200℃ for 0.5 hours, then gradually heated to 220℃ for 1.2 hours, and then heated to 220-240℃ for 2.5 hours. When the esterification rate is >95%, the reaction is terminated. Then 30ppm of tetrabutyl titanate and 60ppm of triphenyl phosphate are added, the temperature is continued to be raised and the pressure is slowly reduced, the speed is adjusted to 40rpm, the temperature is controlled to between 250 and 260℃, and the pressure is gradually reduced to below 100Pa for polycondensation reaction. Sampling analysis was performed, and when the polymer viscosity reached 0.25-0.5 dl / g, stirring was stopped, vacuum was eliminated, and the product was discharged to obtain thermosetting resin A2. Among them, according to the above preparation method, samples 5-8 were prepared according to different molar ratios of raw materials, and the specific feeding information and product indicators are shown in Table 2.

[0222] Table 2

[0223]

[0224] The preparation method of the thermosetting resin A3 is as follows.

[0225] The acid components of terephthalic acid (TPA), 1,4-cyclohexanedicarboxylic acid (CHDA), sebacic acid (SA), the alcohol components of 1,4-cyclohexanedimethanol (CHDM), hexanediol (HD), and 100ppm of zinc acetate were put into a 2L stainless steel reactor, stirred at 50rpm under nitrogen protection, and quickly heated to 180-200℃ for 0.5 hours, then gradually heated to 220℃ for 1.2 hours, and then heated to 220-240℃ for 2.5 hours. When the esterification rate is >95%, the reaction is terminated. Then 30ppm of tetrabutyl titanate and 60ppm of triphenyl phosphate are added, the temperature is continued to rise and the pressure is slowly reduced, the speed is adjusted to 40rpm, the temperature is controlled to between 250 and 260℃, and the pressure is gradually reduced to below 100Pa for polycondensation reaction. Sampling analysis was performed. When the polymer viscosity reached 0.7-2.0 dl / g, stirring was stopped, vacuum was eliminated, and the product was discharged to obtain thermosetting resin A3. Among them, according to the above preparation method, samples 9-10 were prepared according to different molar ratios of raw materials. The specific feeding information and product indicators are shown in Table 3:

[0226] Table 3

[0227]

[0228] The preparation method of thermosetting resin B is as follows:

[0229] The acid components of terephthalic acid (TPA), isophthalic acid (IPA), alcohol components of ethylene glycol (EG), ethylene glycol diglycidyl ether (GDE), neopentyl glycol (NPG), and 100ppm of zinc acetate were put into a 2L stainless steel reactor, stirred at 50rpm under nitrogen protection, and quickly heated to 180-200℃ for 0.5 hours, then gradually heated to 220℃ for 1.2 hours, and then heated to 220-240℃ for 2.5 hours. When the esterification rate is >95%, the reaction is terminated. Then 30ppm of tetrabutyl titanate and 60ppm of triphenyl phosphate are added, the temperature is continued to rise and the pressure is slowly reduced, the speed is adjusted to 40rpm, the temperature is controlled to between 250 and 275℃, and the pressure is gradually reduced to below 100Pa for polycondensation reaction. Sampling analysis was performed, and when the polymer viscosity reached 0.7-1.0 dl / g, stirring was stopped, vacuum was eliminated, and the product was discharged to obtain thermosetting resin B. Among them, according to the above preparation method, samples 13-15 were prepared according to different molar ratios of raw materials, and the specific feeding information and product indicators are shown in Table 4.

[0230] Table 4

[0231]

[0232] The preparation method of liquid coating is as follows:

[0233] Sample 2 (40 parts), sample 6 (20 parts), sample 10 (10 parts), sample 14 (35 parts), auxiliary agent (5 parts, including light stabilizer (770) 1 part, ultraviolet absorber (UV5411) 0.5 parts, antioxidant (1010) 0.5 parts, anti-hydrolysis agent (carbodiimide) 1 part, leveling agent (BYK-333) 0.5 parts, silane coupling agent (KH560) 1.5 parts), ethyl acetate (75 parts) and blocked isocyanate curing agent TKA-75S (5 parts), methylhexahydrophthalic anhydride (3.5 parts), triethanolamine (0.2 parts) were mixed uniformly to obtain the desired liquid coating.

[0234] The liquid coatings of Examples 2 to 14 and Comparative Examples 1 to 6, 10 and 11 were prepared according to the preparation method of Example 1, wherein the components and amounts of the accelerator, auxiliary agent and organic solvent were the same as those of Example 1. The specific component contents of each example and comparative example are shown in Table 5.

[0235] Table 5

[0236]

[0237]

[0238] Test Example 1

[0239] 1. Preparation of photovoltaic modules containing liquid coatings prepared in Examples 1 to 14 and Comparative Examples 1 to 6, 10 and 11

[0240] (1) Coating, drying and pre-curing: The liquid coatings prepared in Examples 1 to 14 and Comparative Examples 1 to 6, 10 and 11 were uniformly coated on the glass fiber composite board by a coating machine, and the coatings were fully infiltrated into the glass fiber layer. The coatings were baked at 85° C. for 3 min to obtain a glass fiber composite board with a certain degree of cross-linking.

[0241] (2) Hot pressing: The glass fiber composite board, the first adhesive film layer, the battery string layer, the second adhesive film layer and the back plate layer are placed in a vacuum laminator from top to bottom for lamination. The lamination includes a first heating stage, a second heating stage and a third pressurized cooling stage. The heating temperature of the first heating stage is 80°C and the heating time is 75s; the heating temperature of the second heating stage is 120°C and the heating time is 110s; the cooling temperature of the third pressurized cooling stage is 40°C, the applied pressure range is 0.2Mpa, and the time is 55s.

[0242] (3) Post-curing: The laminated photovoltaic module is placed in a 105°C curing chamber for further curing for 60 minutes to obtain a photovoltaic panel module.

[0243] 2. Performance Testing

[0244] In order to verify the technical effect of the present application, the present application conducted relevant performance tests on the photovoltaic modules containing the liquid coatings of Examples 1 to 14 and Comparative Examples 1 to 6, 10 and 11 prepared above, and the test results are shown in Table 6.

[0245] Impact resistance test: The test standard of falling ball impact performance is carried out in accordance with GB / T 30984.1 2015 (using a 1040g steel ball and the falling ball height when the sample is destroyed).

[0246] UV radiation aging: According to the QUV UV test method in IEC 62788-7, the UV light intensity is 65W / m 2 , blackboard temperature 60±5℃, UV irradiation 4000 hours. Use spectrophotometer to detect the yellow index b* value of the coating, calculate the change Δb before and after aging, Δb exceeding 3 is unqualified.

[0247] Resistance to hot and cold cycle aging: According to the hot and cold cycle test method required by the IEC61215 standard, the photovoltaic modules are placed in a hot and cold shock test chamber with a relative humidity of less than 60%, and the temperature is continuously cycled between (–40±2)℃ and (85±2)℃ for 200 times. The holding time at the two extreme temperatures is 15 minutes, and one cycle is about 4 hours. The appearance and power of the modules before and after the hot and cold cycle test are tested. If the appearance is significantly damaged, it is unqualified; the power attenuation ratio is calculated, and it is unqualified if it exceeds 5%.

[0248] Peel force test: the front plate sample was cut into samples of 1 cm × 20 cm in size, the glass fiber reinforcement layer and the polyester composite layer were peeled off, and the peel force was tested at 180° with a peel rate of 100 mm / min. The equipment used was Shimadzu tensile testing machine, model AGS-1KN.

[0249] Visible light transmission rate: After UV aging for 200KWh, using a spherical ultraviolet spectrophotometer (Shimadzu, Japan), visible light band 400 ~ 1100cm -1 Test light transmittance within the range.

[0250] Table 6

[0251]

[0252]

[0253] It can be seen from the above test data that, compared with the comparative example, the photovoltaic modules comprising the liquid coatings of Examples 1 to 14 have excellent impact resistance, UV aging resistance, and hot and cold cycle aging resistance, and have high visible light transmittance and excellent adhesion, meeting the use standards.

[0254] According to the above-mentioned photovoltaic module preparation method, the liquid coating prepared in Example 1 was subjected to different process conditions (different process conditions are shown in Table 7) to prepare photovoltaic modules of Examples 15 to 21 and Comparative Examples 7 to 9.

[0255] Table 7

[0256]

[0257] Test Example 2

[0258] The photovoltaic modules prepared in Examples 15 to 21 and Comparative Examples 7 to 10 were subjected to the above-mentioned performance tests, respectively. The test results are shown in Table 8.

[0259] Table 8

[0260]

[0261] As shown in Table 8, the photovoltaic modules prepared in Examples 15 to 21 have excellent impact resistance, UV aging resistance, and cold and hot cycle aging resistance, and have high visible light transmittance and excellent bonding strength. Compared with Example 7, Example 1 has poor impact resistance of the photovoltaic module prepared in Example 7 due to different drying temperatures, significant yellowing after UV aging, large power attenuation, unstable bonding strength, and low visible light transmittance. Compared with Example 8, Example 21 and Example 8, and Example 20 and Example 9, the photovoltaic modules prepared in Examples 8 and 9 have poor impact resistance, significant yellowing after UV aging, large power attenuation, and low visible light transmittance due to different post-curing times.

[0262] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A liquid coating, characterized in that: The raw materials for preparing the liquid coating include thermosetting resin A, thermosetting resin B and curing agent, wherein: The thermosetting resin A is a hydroxyl super weather-resistant polyester resin and / or a carboxyl super weather-resistant polyester resin, the hydroxyl value of the hydroxyl super weather-resistant polyester resin is in the range of 5 to 25 mgKOH / g, and the acid value of the carboxyl super weather-resistant polyester resin is in the range of 5 to 15 mgKOH / g; The thermosetting resin B is a modified weather-resistant polyester resin.

2. The liquid coating according to claim 1, characterized in that The modified weather-resistant polyester resin has a hydroxyl value in the range of 5 to 10 mgKOH / g and an acid value in the range of 5 to 10 mgKOH / g; Preferably, the weight proportion of the thermosetting resin A is 50 to 100 parts, preferably 50 to 98 parts, and more preferably 50 to 95 parts; Preferably, the weight proportion of the thermosetting resin B is 20 to 50 parts, preferably 25 to 45 parts; Preferably, the modified weather-resistant polyester resin is a polyester resin modified with malonic acid or a malonic acid derivative and / or an epoxy-modified polyester resin. Further preferably, the malonic acid derivative is selected from one or more of dimethyl malonate, diethyl malonate and monomethyl malonate.

3. The liquid coating according to claim 1 or 2, characterized in that: The thermosetting resin A is a copolyester resin obtained by the reaction of a dibasic acid and a diol; Preferably, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid, cyclohexanedicarboxylic acid, adipic acid and sebacic acid; Preferably, the diol is selected from one or more of ethylene glycol, propylene glycol, neopentyl glycol, cyclohexanedimethanol and hexanediol; Preferably, the molar ratio of the dibasic acid to the diol is 1:1.3-2; more preferably 1:1.4-1.7; Preferably, the thermosetting resin A is selected from one or more of thermosetting resin A1, thermosetting resin A2 and thermosetting resin A3; Preferably, in the preparation of the raw material of the thermosetting resin A1, the dibasic acid is selected from one or more of terephthalic acid, isophthalic acid and adipic acid, and the diol is selected from ethylene glycol and / or neopentyl glycol; Preferably, in the preparation of the raw material of the thermosetting resin A2, the dibasic acid is selected from one or more of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexylene glycol and / or neopentyl glycol; Preferably, in the preparation of the raw material of the thermosetting resin A3, the dibasic acid is selected from one of terephthalic acid, cyclohexanedicarboxylic acid and sebacic acid, and the diol is selected from hexanediol and / or cyclohexanedimethanol; Preferably, the glass transition temperature of the thermosetting resin A1 is in the range of 55 to 75° C., more preferably 56 to 75° C., and even more preferably 60 to 75° C.; Preferably, the relative molecular weight of the thermosetting resin A1 is in the range of 15000 to 20000; more preferably, in the range of 15500 to 19000; and even more preferably, in the range of 16500 to 19000; Preferably, the weight proportion of the thermosetting resin A1 is 30 to 55 parts, preferably 35 to 55 parts; Preferably, the glass transition temperature of the thermosetting resin A2 is in the range of 25 to 45°C, more preferably in the range of 26 to 45°C, and even more preferably in the range of 30 to 45°C; Preferably, the relative molecular weight of the thermosetting resin A2 is in the range of 5000-10000; more preferably, it is in the range of 6000-10000; and even more preferably, it is in the range of 8000-10000; Preferably, the weight proportion of the thermosetting resin A2 is 15 to 30 parts, preferably 15 to 25 parts; Preferably, the glass transition temperature of the thermosetting resin A3 is in the range of -10 to 10°C, more preferably -8 to 10°C, and even more preferably -5 to 10°C; Preferably, the relative molecular weight of the thermosetting resin A3 is in the range of 15000-40000; more preferably, it is in the range of 18000-30000; and even more preferably, it is in the range of 19000-25000; Preferably, the weight proportion of the thermosetting resin A3 is 5 to 15 parts, preferably 6 to 15 parts.

4. The liquid coating according to any one of claims 1 to 3, characterized in that The curing agent includes curing agent 1 and curing agent 2, wherein the curing agent 1 is an isocyanate curing agent, preferably one or more of blocked isocyanate and open isocyanate, and further preferably one or more of TMA-100, TLA-100, TUL-100, TKA-75S, and TPA-B80X; Preferably, the amount of curing agent 1 added is 5-10% of the mass of the thermosetting resin A, preferably 5-9%, and more preferably 6-8%; The curing agent 2 is selected from one or more monomers or modified monomers and anhydride curing agents that can be cured by Michael addition reaction; more preferably, the curing agent 2 is selected from one or more of methyl hexahydrophthalic anhydride, phthalic anhydride, trimellitic anhydride, tetrahydrophthalic anhydride, and vinyl-terminated resin; more preferably, glycidyl methacrylate and / or methyl hexahydrophthalic anhydride; Preferably, the added amount of the curing agent 2 is 5-15% of the mass of the thermosetting resin B, preferably 6-12%, and more preferably 8-12%.

5. The liquid coating according to any one of claims 1 to 4, characterized in that The raw materials for preparing the liquid coating also include organic solvents, additives and accelerators; Preferably, the organic solvent is selected from one or more of butanone, ethyl acetate and methyl acetate; more preferably, it is one of butanone, ethyl acetate and methyl acetate; Preferably, the weight proportion of the organic solvent is 50 to 100 parts, preferably 60 to 100 parts, more preferably 60 to 90 parts, and even more preferably 60 to 80 parts; Preferably, the auxiliary agent is selected from one or more of UV absorbers, UV stabilizers, defoamers, leveling agents, catalysts, anti-hydrolysis agents, and antioxidants; Preferably, the weight proportion of the auxiliary agent is 5 to 10 parts, preferably 5 to 8 parts, and more preferably 5 to 7 parts; Preferably, the accelerator is one or more of a tertiary amine accelerator or an epoxy resin curing accelerator; Preferably, the weight proportion of the accelerator is 0.1 to 0.5 parts, preferably 0.1 to 0.4 parts, and more preferably 0.1 to 0.3 parts.

6. A method for preparing a liquid coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: Thermosetting resin A, thermosetting resin B, organic solvent, auxiliary agent, curing agent and accelerator are mixed uniformly to obtain the liquid coating.

7. Use of the liquid coating according to any one of claims 1 to 5 in preparing a photovoltaic module.

8. A method for preparing a photovoltaic module comprising the liquid coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing thermosetting resin A, thermosetting resin B, organic solvent, additive, curing agent and accelerator in proportion to obtain a desired liquid coating; (2) evenly coating the liquid coating obtained in step (1) on the glass fiber composite board and baking to obtain the glass fiber composite board; (3) stacking the glass fiber composite board obtained in step (2), the first adhesive film layer, the battery string layer, the second adhesive film layer and the back plate layer in sequence from top to bottom and laminating them; (4) Post-curing the photovoltaic module laminated in step (3) to obtain the photovoltaic module.

9. The method for preparing a photovoltaic module according to claim 8, characterized in that: In step (2), the baking is carried out at 80-100° C. for 1.5-5 min, preferably at 85-100° C. for 1.5-5 min; Preferably, in step (3), the lamination process includes a first heating stage, a second heating stage and a third pressurized cooling stage; Preferably, the heating temperature in the first heating stage is 80-110°C, preferably 80-100°C, and more preferably 80-90°C; Preferably, the heating time of the first heating stage is 50 to 100 s, preferably 50 to 90 s, more preferably 50 to 80 s, and even more preferably 60 to 80 s; Preferably, the heating temperature in the second heating stage is 110-140°C, preferably 110-130°C, and more preferably 110-125°C; Preferably, the heating time of the second heating stage is 100 to 200 s, preferably 100 to 180 s, more preferably 100 to 150 s, and even more preferably 100 to 140 s; Preferably, the temperature of the third pressurized cooling stage is controlled to be 10 to 50° C., preferably 20 to 50° C., and more preferably 30 to 50° C.; Preferably, the time of the third pressurized cooling stage is controlled to be 30 to 60 seconds, preferably 35 to 60 seconds, more preferably 40 to 60 seconds, and even more preferably 45 to 60 seconds; Preferably, the pressure in the third pressurized cooling stage is controlled to be 0.05 to 0.25 MPa, preferably 0.1 to 0.25 MPa, and more preferably 0.15 to 0.25 MPa; Preferably, in step (4), the post-curing temperature is controlled to be 90 to 120° C., preferably 90 to 110° C., and more preferably 100 to 110° C.; Preferably, in step (4), the post-curing time is controlled to be at least 30 minutes, preferably 30 to 60 minutes.

10. A photovoltaic module obtained according to the preparation method of claim 8 or 9.

Citation Information

Patent Citations

  • Back film of solar cell and preparing technique thereof

    CN101290950B

  • Solar battery back plate adopting ultraviolet (UV) curing weather-proof coating and manufacture method of solar battery back plate

    CN102610680A

  • Weatherable sheet for solar cell module, product obtained using the sheet, and process for producing the weatherable sheet for solar cell module

    CN102712184A

  • Back sheet for solar cell module and solar cell module

    CN102969382B

  • Solar panel back film and manufacturing technology thereof

    CN103346182A